Base nutricional de la especie invasora lithobates catesbeianus (rana toro) - Mero Cheme, Steeven Santiago (Machala : Universidad Técnica de Machala, 2024)
He studied the most frequent feeding of the bull frog Lithobates catesbeianus, based on the finding of the stomach contents of 77 individuals, collected in two different localities of the Costa region. It was observed that the highest proportion of ingested was of arthropods and molluscs, identifying a total of 19 dams corresponding to Pomacea canaliculata (apple snail), being the mollusks more frequently found and 15 prey of crustacean decapod, belonging to the species Cherax quadricarinatus (lobster Australian). This species showed no preference for any of the types of prey, which indicates a general diet. in the Babahoyo area, of the 24 individuals analyzed, 83.3% corresponded to stomachs containing insects, in a state of decomposition, which could not be identified and 16.7% had stomachs with prey such as the apple snail and the Australian lobster and in the Yaguachi area, of the 53 specimens analyzed, 60.4% presented stomachs with prey such as the apple snail and the Australian lobster and 39.6% corresponded to subjects with stomachs with insects in a state of decomposition. They could not be identified.
Sé estudió la alimentación más frecuente de la rana toro Lithobates catesbeianus, en base al hallazgo de los contenidos estomacales de 77 individuos, colectados en dos diferentes localidades de la región Costa. Se observó que la mayor proporción de ingesta fue de artrópodos y moluscos, identificándose un total de 19 presas correspondientes a Pomacea canaliculata (caracol manzana), siendo los moluscos más frecuentemente encontrados y 15 presas de crustáceo decápodo, perteneciente a la especie Cherax quadricarinatus (langosta australiana). Esta especie no mostró preferencia por ninguno de los tipos de presa, lo cual indica una dieta generalista, en la zona de Babahoyo, de los 24 individuos analizados el 83,3% corresponde a estómagos que contenían insectos, en estado de descomposición, que no se pudieron identificar y el 16,7% presentaron estómagos con presas como el caracol manzana y la langosta australiana y en en la zona de Yaguachi, de los 53 especímenes analizados el 60,4 % presentaron estómagos con presas como el caracol manzana y la langosta australiana y el 39, 6 % corresponde a sujetos con estómagos con insectos en estado de descomposición que no se pudieron identificar.
Keywords: HALLAZGOS; INGESTA; CARACOL MANZANA; ARTRÓPODOS